Introducing a sustainability assessment index metric: a simplified sustainability assessment approach - AbdlMonem H. Beitelmal (Discover Sustainability)
Abstract Sustainability is a broad concept that drives global efforts to mitigate climate change, reduce environmental impacts, and improve societal well-being. However, its practical application remains challenging, largely due to the absence of standardized sustainability assessment frameworks and reliable indices that consistently evaluate its impact across diverse sectors. This paper presents a structured sustainability assessment methodology that employs aggregated metrics to evaluate impacts across key sustainability categories. The methodology is implemented in a simplified assessment tool designed to assess the potential societal, environmental, and economic impacts of built environment projects. This tool enables informed decision-making by identifying potential consequences of proposed changes and ensuring that critical sustainability considerations are addressed. To overcome challenges associated with limited historical project data, the methodology integrates standardized evaluation questionnaires that capture potential impacts across essential sustainability categories. Evaluators assess both the type (positive or negative) and magnitude of each impact. The proposed Sustainability Assessment Index (SAI) balances impact across environmental, economic, and societal categories and quantifies the overall average sustainability impact on a scale from − 3 (most negative) to + 3 (most positive), with “NA” assigned for non-applicable indicators. In addition, a weighted sustainability assessment index (WSAI) and the multi-weight sustainability assessment index (MWSAI) are introduced, allowing evaluators to apply weighting coefficients to each impact based on its relative importance. The additional proposed refinements enhance the flexibility and robustness of the assessment as more data becomes available. This approach enables evaluators and stakeholders to assess, track, and benchmark sustainability impacts, identify areas for improvement, and support more sustainable decision-making in built environment projects. A case study of the Qatar Underground Metro Project is presented to demonstrate the practical application of this methodology, illustrating its potential to optimize sustainability assessment through a comprehensive analysis of societal, environmental, and economic impacts.